2016
DOI: 10.1139/cjm-2016-0229
|View full text |Cite
|
Sign up to set email alerts
|

Estimating genetic structure and diversity of cyanobacterial communities in Atlantic forest phyllosphere

Abstract: Cyanobacterial communities on the phyllosphere of 4 plant species inhabiting the endangered Brazilian Atlantic Forest biome were evaluated using cultivation-independent molecular approaches. Total genomic DNA was extracted from cells detached from the surface of leaves of Euterpe edulis, Guapira opposita, Garcinia gardneriana, and Merostachys neesii sampled in 2 Brazilian Atlantic Forest locations along an elevational gradient, i.e., lowland and montane forest. The DNA fingerprinting method PCR-DGGE revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 41 publications
0
12
0
2
Order By: Relevance
“…M. neesii exhibits higher cyanobacteria abundance and a larger number of diazotrophs affiliated to the order Nostocales (Rigonato et al, 2016) than E. edulis and other species from the same area (Gómez, 2012). Its phyllosphere harbored high annual BNF rates (∼60 kg N ha −1 y −1 ), almost equal to the rate reported for evergreen tropical forests (Reed, Cleveland & Townsend, 2011), but significantly higher than those observed for Spathacanthus hoffmannii (Acanthaceae), Chamaedorea tepejilote (Arecaceae), Brosimum utile (Moraceae), Caryocar costaricense (Caryocaraceae), Staminodella manilkara (Sapotaceae), Qualea paraensis (Vochysiaceae) and Schizolobium parahybum (Fabaceae) (between 0.035 and 5 kg N ha −1 y −1 —Freiberg, 1998; Reed, Cleveland & Townsend, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…M. neesii exhibits higher cyanobacteria abundance and a larger number of diazotrophs affiliated to the order Nostocales (Rigonato et al, 2016) than E. edulis and other species from the same area (Gómez, 2012). Its phyllosphere harbored high annual BNF rates (∼60 kg N ha −1 y −1 ), almost equal to the rate reported for evergreen tropical forests (Reed, Cleveland & Townsend, 2011), but significantly higher than those observed for Spathacanthus hoffmannii (Acanthaceae), Chamaedorea tepejilote (Arecaceae), Brosimum utile (Moraceae), Caryocar costaricense (Caryocaraceae), Staminodella manilkara (Sapotaceae), Qualea paraensis (Vochysiaceae) and Schizolobium parahybum (Fabaceae) (between 0.035 and 5 kg N ha −1 y −1 —Freiberg, 1998; Reed, Cleveland & Townsend, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Studying the same bamboo species, Rigonato et al (2016) reported a high abundance of cyanobacteria from the diazotrophic order Nostacales. In this AF area, unlike several other studies (Tabarelli & Mantovani, 2000; Griscom & Ashton, 2003; Lima et al, 2012), the presence of M. neesii in a pristine montane forest does not seem to alter the overall forest structure and diversity (Padgurschi et al, 2011), carbon and nitrogen stocks (Vieira et al, 2011) or tree biomass (283.2 Mg ha −1 ) (Alves et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, bryophytes may also play a role in leaf nitrogen balance either by reciprocally transferring nitrogen to host leaves (Wanek & Portl, ) or creating favorable microclimatic conditions for cyanobacteria (Bentley, ; Turetsky, ). Microbial assemblages such as biofilms harboring cyanobacteria and other nitrogen fixing bacteria, including endophytic bacteria, might also transfer nitrogen to the leaf (Coley & Kursar, ; Moyes et al ., ; Rigonato et al ., ; Lambais et al ., ). In this line, Laforest‐Lapointe et al .…”
Section: Phyllosphere Traits As the Missing Link Among Axes Of Plant mentioning
confidence: 97%
“…However, bryophytes may also play a role in leaf nitrogen balance either by reciprocally transferring nitrogen to host leaves (Wanek & Portl, 2005) or creating favorable microclimatic conditions for cyanobacteria (Bentley, 1987;Turetsky, 2003). Microbial assemblages such as biofilms harboring cyanobacteria and other nitrogen fixing bacteria, including endophytic bacteria, might also transfer nitrogen to the leaf (Coley & Kursar, 1996;Moyes et al, 2016;Rigonato et al, 2016;Lambais et al, 2017). In this line, Laforest-Lapointe et al (2017), using a tree biodiversity-ecosystem functioning experiment, have shown that plant community productivity is positively related to phyllosphere bacterial diversity indicating the importance of the interplay of plant-phyllosphere for ecosystem functioning.…”
Section: Phyllosphere Traits As the Missing Link Among Axes Of Plant mentioning
confidence: 99%